Management of Asian soybean rust with Bacillus subtilis in sequential and alternating fungicide applications - Dorighello, Dalton Vinicio [UNESP]; Forner, Cassiano [UNESP]; Boas de Campos Leite, Regina Maria Villas; Bettiol, Wagner (Springer, 2020)
Since it was first reported in Brazil, Asian soybean rust has been considered the most significant disease in the crop. Successive applications of fungicides during the crop cycle have been the most efficient control measures. Considering the occurrence of Phakopsora pachyrhizi populations with less sensitivity to the main recommended fungicide molecules, which results in lower control efficiency, as well as difficulties in obtaining new molecules, it is important that new tools be tested for integration into a management program. In field conditions, the efficiencies of one biological product based on Bacillus subtilis and another based on roasted coffee bean oils were studied in sequential and alternating applications with the fungicide pyraclostrobin + epoxiconazole. The application schedules of B. subtilis and chemical fungicide products in both trials reduced the area under the disease progress curve and increased the yield, the weight of 100 seeds, and the normalized difference vegetation index when compared to the control. B. subtilis and fungicides applied in sequence reduced the area under the disease progress curve 41% to 53% and 67% to 69% in the first and second assays, respectively. The applications of coffee oil alone or alternate with fungicide did not increased productivity compared to the control in the two fields. These results were obtained under conditions with a low intensity of disease, and therefore, different responses may be found under high intensity levels. These results allow us to suggest the use of products based on B. subtilis in soybean rust management programs along with chemical fungicides under low-medium disease pressure.
Keywords: Bacillus; Glycine max; Phakopsora pachyrhizi; Biocontrol; Coffee oil